Modelling of a power system for a new airborne radar system using Saber® Focused on the Multiphase Transformer Rectifier Unit - Bergqvist, Andreas; Janehag, Niklas (My University, 2009)
This M.Sc. thesis focuses on the modelling and verification of a 54-pulse step-down AutoTransformer Rectifier Unit (ATRU) used in the power system of the airborne early warning and control system ERIEYE®. A BLDC generator and a PI-controller with abc to dq transformation is designed in Saber® and used in the implementation of the entire radar power system supplying three power units mainly consisting of large capacitor banks and step-down DC/DC converters as loads. The system using a 54-pulse step-down ATRU has been evaluated and compared to an older system incorporating 6-pulse rectification and it was clearly seen that using the newer system improves the quality of the current drawn from the BLDC generator. The 5th and 7th harmonic of the voltage and current were reduced by 90%. The M.Sc. thesis has also resulted in a fully functioning and verified model of the 54-pulse step-down ATRU with a PI-controlled BLDC generator and three power units as loads. An evaluation of sharing and administrating Saber® models within a company with high security demands has been carried out. It was shown that this can be done in a safe and effective way.
Keywords: Elkraftteknik; Electric power engineering